'In the Light of Leibniz and Lucretius': An Encounter between Deleuze and New Materialism. Issue 4 (November 2021) - Berressem, Hanjo
Abstract : While most new materialists, including Thomas Nail, tend to distance themselves from Deleuze, this essay reads the encounter of Nail's 'process materialism' and Deleuzian philosophy as productive rather than contentious. After tracing the affinities of their notions of continuity and discontinuity by way of Deleuze's The Fold: Leibniz and the Baroque and Nail's Lucretius I: An Ontology of Motion and Being and Motion, the essay considers Nail's unfolding of Lucretius' luminous philosophy in relation to Deleuze's reading of Lucretius from within Deleuze's own 'philosophical luminism'. Within the multiple overlaps between Nail and Deleuze, particularly vis-à-vis quantum physics and quantum field theory, their divergent readings of the particle–wave duality bring about a productive conceptual tension. Nail's argument about the ontological precedence of waves over particles ('process precedes existence') is illuminated by Deleuze's concept of their ontological complementarity (actual particles and virtual waves, virtual particles and actual waves), and vice versa.